Positive Discipline and Work Performance of Public Elementary School Teachers - Olaño, Merrycris (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study determined the extent of effects of positive discipline on the work performance of public elementary school teachers in Baras District, Division of Rizal, during School Year 2025–2026. Specifically, it examined the perceived effects of positive discipline in terms of classroom environment, instructional delivery, teacher-pupil relationship, collaboration and communication, and conflict resolution, and determined whether significant differences existed when perceptions were grouped according to selected demographic and professional characteristics. It also assessed teachers’ level of work performance based on their Individual Performance Commitment and Review (IPCR) ratings and examined the relationship between positive discipline and work performance. The study employed a descriptive survey research design and documentary analysis. The respondents consisted of the total population of 325 public elementary school teachers from eleven elementary schools in Baras District. Data were gathered using a researcher-made questionnaire-checklist, while teachers’ latest IPCR ratings served as the basis for determining their work performance. Findings revealed that most respondents were 31–40 years old, female, single, Teacher I, holders of a bachelor’s degree or with master’s units, had 11–20 years of teaching experience, and had attended school-level in-service training. Teachers perceived positive discipline as having a very high effect on classroom environment, instructional delivery, teacher-pupil relationship, and collaboration and communication. Significant differences in perceived effects were found according to age, civil status, educational attainment, and in-service training attendance, but not according to sex, position title, and length of service. Teachers demonstrated very satisfactory work performance based on their IPCR ratings. However, no significant relationship was found between the perceived effects of positive discipline and teachers’ level of work performance. The study recommends sustained professional development, Learning Action Cell sessions, and strengthened school-based initiatives on positive discipline. The proposed action plan may also be implemented to support its continuous and effective application.